Analisis Pemahaman dan Praktik Pengelolaan Keuangan pada Umkm Es degan Bu Ulfa Sidoarjo - Nifhfu Lailaturohma; Chairil Anwar; Laily Muzdalifah (CV. ALIM'SPUBLISHING, 2026)
This study aims to analyze the financial management practices of the Es Degan Bu Ulfa MSME and their compliance with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). The study used a qualitative approach with a case study method. Data were obtained through interviews and observations, then analyzed descriptively and qualitatively. This study aims to analyze the financial management practices of the Es Degan Bu Ulfa MSME and their compliance with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). The study used a qualitative approach with a case study method. Data were obtained through interviews and observations, then analyzed descriptively and qualitatively. The results indicate that financial management is still carried out simply and does not yet implement written records. Business income and expenses still rely on memory, even though business owners perform daily profit and loss calculations and separate personal and business finances. The main obstacles faced include limited human resources and a low understanding of financial record keeping and the SAK EMKM. Based on the analysis, financial management practices are not fully compliant with SAK EMKM standards. Therefore, the implementation of simple financial record keeping is necessary to structure business financial information and support business decision-making. Proper financial management can help improve business performance, monitor cash flow, evaluate profitability, and enhance accountability. Furthermore, the application of SAK EMKM is expected to facilitate access to financing and strengthen the sustainability and competitiveness of MSMEs in an increasingly competitive business environment.